Method for measuring mechanical power during the vertical jump. - Carrasco Sosa, S.; Gaitán González, M.; González Camarena, R.; Yáñez Suarez, O. (Revista Mexicana de Ingenieria Biomedica, 2018)
The muscular powers of the phases of extension and braking, during the realization of a vertical jump of maximum intensity, were valued by the measurement of 3 times: flight extension and braking. Flight time was recorded through a contact platform, and flexion and extension times with a knee electrogonometer. The calculations were made with a computerized system. Two protocols were tested, simple and consecutive jumps, only the first being repeatable.